Pendekatan Demonstrasi Afeksional Terhadap Pemahaman Materi Unsur-Unsur Geografis Dan Penduduk Pada Mata Pelajaran Ilmu Pengetahuan Sosial - Zakiah, Umi (Universitas Darul Ulum, 2022)
Increasing the material understanding of the relationship between geographic and population elements in Social Science Subjects (IPS) through the application of an affective demonstration approach is very important because of the low understanding of students. The purpose of this study was to obtain a comprehensive data description of teaching and learning activities (KBM) to increase understanding of the material connection between geographical elements and residents using an affective demonstration approach in Social Science Subjects (IPS) Class VIII-C MTs Negeri Tembelang 2030 Academic Year /2021, both during pre-research, research process, and post-research. With the class action research method. The result obtained is that there is an increase in students' understanding of the material related to geographic and population elements in Social Science Subjects (IPS) seen in the active participation of students in the stages of the learning cycle. Student activities such as (1) listening to the teacher's description of the subject matter; (2) doing practical activities and practice questions in the first assignment; (3) do practical activities and practice questions in the second assignment; and (4) carry out a joint evaluation to get the right conclusions from the learning activities that have just been carried out which is a form of active participation of students in teaching and learning activities (KBM) of Social Science Subjects (IPS) adequately with evidence of a value exceeding the completeness score namely 74. And an increase in students' understanding of the material related to geographical elements and residents in teaching and learning activities (KBM) Social Science Subjects (IPS) is also implemented in a real way to concrete results such as the ability to understand the material related to geographical elements and population in Social Science Subjects (IPS) in the form of enrichment questions that focus on aspects of improving the material properly and correctly.